Edukasi Dan Pelatihan Administrasi Terhadap Santri Putri Pondok Pesantren Mbah Ashfiya’ Di Desa Pranggang Kecamatan Plosoklaten Kabupaten Kediri - Qurrotul Muzdalifah; Uzeir Mustaghfirin (LP3M IAIFA Kediri, 2021)
Financial statements are basically the result of an accounting process that can be used as a tool to communicate financial data or company activities to interested parties. The financial statements were also prepared by the student daughter of Pondok Pesantren Mbah Ashfiya' as one of the business responsibilities that have been carried out which will later be reported to the caretaker of Pondok Pesantren Mbah Ashfiya'. In addition, financial statements are also useful to find out the real condition of business finance, regulate and control financial transactions that occur throughout the overall sustainability of the business. Financial statements can also be the basis of economic decision making in business management such as pricing and others. But in its realization, the student daughter of Pondok Pesantren Mbah Ashfiya' had difficulty in terms of making simple financial statements and transaction bookkeeping. Therefore, researchers took the initiative to conduct